Ductus Omphalocele Mesenteric Persisten: A Case Reports - Siwi Bagus Ajiningrat; Nunik Agustriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The ductus omphalomecenterica is a normal embryological structure where it serves to connect the midgut of the fetus to the yolk sac. Usually, this ductus will disappear at 9 weeks gestation. However, if this condition does not occur, then it can cause various anomalies to appear in the fetus. Case Presentation: The patient was reported to be hospitalized with the chief complaint of choking. Echocardiography examination with the results of the examination found the presence of cyanotic congenital heart disease (CHD). The patient was referred to pediatric surgery with a diagnosis of persistent mesenteric duct omphalocele. Terminal ileum anastomoses resection laparotomy was performed. Conclusion: After surgery due to complications of pneumonia and sepsis, the patient died.